Pancasila Sebagai Dasar Anti Korupsi - Azami, Mohammad Khoiron (Maliki Interdisciplinary Journal, 2025)
Corruption is a fundamental problem that hinders national progress, damages social relations, and undermines democracy. In Indonesia, corruption not only harms state finances but also erodes public trust in the government and undermines moral values ​​within society. Pancasila, as the foundation of the state and the nation's way of life, encompasses moral, ethical, and spiritual values ​​that can serve as a strong foundation for preventing and overcoming corruption. This article examines this issue in depth by analyzing six published scientific journals. The results show that each principle of Pancasila has values ​​that can be applied to public policy, education, law enforcement, and the development of an anti-corruption culture. This study also emphasizes that education based on Pancasila values ​​and moral strengthening are crucial steps in shaping a society with integrity. By consistently implementing Pancasila values, Indonesia can strengthen its anti-corruption system comprehensively, both structurally and actually.